2017
DOI: 10.22158/ra.v2n2p19
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Fruit Quality of Strawberry (Frageria ananasa Dutch) under Different Phosphorus Levels

Abstract: Strawberry fruit takes less time for production and is easily multiplied. Fruiting is an exhaustive process and depletes nutrients especially phosphorus as it is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…P negatively influenced titratable acidity, a result which agrees with that which has been reported by Obreza [ 53 ] in citrus. In addition, Medeiros et al [ 70 ] and Ahmad et al [ 71 ] also found this effect in strawberry, observing that low concentrations of P produce high titratable acidity in the fruit.…”
Section: Resultsmentioning
confidence: 88%
“…P negatively influenced titratable acidity, a result which agrees with that which has been reported by Obreza [ 53 ] in citrus. In addition, Medeiros et al [ 70 ] and Ahmad et al [ 71 ] also found this effect in strawberry, observing that low concentrations of P produce high titratable acidity in the fruit.…”
Section: Resultsmentioning
confidence: 88%
“…Our study findings have lower values than those of Mattner et al and Çiylez and Eşitken. K is effective in root development [84], and MSWC applications increased K uptake, which had a positive effect on root growth. According to our study findings, root length has an average value, and MSWC applications provide sufficient root length.…”
Section: Plant Growth Parametersmentioning
confidence: 99%
“…Lu et al (2016) evaluated three different sources of Silicon on the agronomic variables of tomato and determined that the application of nanosilica was associated with increased height and dry and fresh weight of plant organs, and consequently with increased yield. Numerous studies suggest that Silicon increases the yield of crops such as strawberry (Ouellette et al, 2017), tomato (Lu et al, 2016;Marodin et al, 2014;Toresano et al, 2012), cucumber (Abd-Alkarim et al, 2017), courgette (Cucurbita pepo) (Savvas et al, 2009), potato (Solanum tuberosum) (Pilon et al, 2013), wheat (Triticum durum) (Hanafy et al, 2008), and other grasses (Ahmad et al, 2017).…”
Section: Mexican Journal Of Phytopathologymentioning
confidence: 99%
“…Similarmente, Lu et al (2016) evaluaron tres fuentes distintas de Silicio sobre variables agronómicas de jitomate y determinaron que la aplicación de nanosilice tiene un mayor impacto en el incremento de altura y en el peso seco y fresco de los órganos, y de manera consecuente del rendimiento. Numerosos estudios sugieren que el Silicio aumenta el rendimiento de cultivos como fresa (Ouellette et al, 2017), jitomate (Lu et al, 2016;Marodin et al, 2014;Toresano et al, 2012), pepino (Abd-Alkarim et al, 2017, calabacín (Cucurbita pepo) (Savvas et al, 2009), papa (Solanum tuberosum) (Pilon et al, 2013), trigo (Triticum durum) (Hanafy et al, 2008) y otras gramíneas (Ahmad et al, 2017).…”
Section: Mexican Journal Of Phytopathologyunclassified